Macro-Particle Charcoal C Content following Prescribed Burning in a Mixed-Conifer Forest, Sierra Nevada, California - Wiechmann, Morgan L.; Hurteau, Matthew D.; Kaye, Jason P.; Miesel, Jessica R. (PloS one, 2015)
Fire suppression and changing climate have resulted in increased large wildfire frequency and severity in the western United States, causing carbon cycle impacts. Forest thinning and prescribed burning reduce high-severity fire risk, but require removal of biomass and emissions of carbon from burning. During each fire a fraction of the burning vegetation and soil organic matter is converted into charcoal, a relatively stable carbon form. We sought to quantify the effects of pre-fire fuel load and type on charcoal carbon produced by biomass combusted in a prescribed burn under different thinning treatments and to identify more easily measured predictors of charcoal carbon mass in a historically frequent-fire mixed-conifer forest. We hypothesized that charcoal carbon produced from coarse woody debris (CWD) during prescribed burning would be greater than that produced from fine woody debris (FWD). We visually quantified post-treatment charcoal carbon content in the O-horizon and the A-horizon beneath CWD (> 30 cm diameter) and up to 60 cm from CWD that was present prior to treatment. We found no difference in the size of charcoal carbon pools from CWD (treatment means ranged from 0.3-2.0 g m-2 of A-horizon and 0.0-1.7 g m-2 of O-horizon charcoal) and FWD (treatment means ranged from 0.2-1.7 g m-2 of A-horizon and 0.0-1.5 g m-2 of O-horizon charcoal). We also compared treatments and found that the burn-only, understory-thin and burn, and overstory-thin and burn treatments had significantly more charcoal carbon than the control. Charcoal carbon represented 0.29% of total ecosystem carbon. We found that char mass on CWD was an important predictor of charcoal carbon mass, but only explained 18-35% of the variation. Our results help improve our understanding of the effects forest restoration treatments have on ecosystem carbon by providing additional information about charcoal carbon content.